Creation of Mortgages on Land in Nigeria: Issues and Challenges - Salawu, Busari Morufu (ABUAD Law Journal, 2025)
The creation of legal mortgages is made complex by the existence of plural legislation1 in the Nigerian legal system. This study conducted an overview of the creation of legal mortgage in Nigeria. It also evaluated challenges posed to it under the Land Use Act 1978.The doctrinal research method was adopted, using primary and secondary sources. The primary source included legislation such as Conveyancing Act 1881, Property Conveyancing Act 1959 and Mortgages and Property Law 2012 and case law. The secondary source included textbooks, journal articles, conference proceedings and the internet. The data collected were subjected to content analysis. It was revealed that plural legislations and inconsistent judicial decisions made the process of creating a legal mortgage cumbersome for the stakeholders. It was equally found that apart from obsolete provisions in the mortgage statutes like Conveyancing Act1881and Property and Conveyancing Law 1959, they had some irreconcilable provisions with the Land Use Act 1978.It was recommended that all the mortgage statutes should be harmonized to a single legislation applicable throughout the federation and the consent provision of the Land Use Act should be expunged and replaced by a faster method under which the Governor could be compelled to act as soon as the grantee fulfils all conditions.